Rumah Kreatif Tamiang: An Inclusive CSR Model For Difabel - Amady, M Rawa El (Jurnal Antropologi: Isu-Isu Sosial Budaya, 2024)
This study discussed the Rumah Kreatif Tamiang programme, which is a disability inclusion programme. This program has an ecosystem-based inclusion approach that focuses on stakeholders. This program is interesting because Law No. 8 of 2016 on disability has not been implemented, especially in Aceh Tamiang. This research is a qualitative study, data was obtained through library and internet research, observation and in-depth interviews with the program manager (CDO), disabled people who run the program, the community, social services, and cafÃ© and workshop customers. This research found that the programme was designed and implemented with a professional approach to stakeholders based on ecosystems and local culture. This study contributes to strengthening mentoring and CSR theories that mentoring and CSR programmes need to be based on local needs and ecosystems with actor-centredness. Programmes can be replicated by other actors, especially businesses, government, universities and the general public.